ANALISIS MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nirmala Putri, Dwi; Sulastri Dewi Rumapea, Vanni; Efendi Hutagalung, Erwin; Muhammadin Al Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education ideally develops students’ cognitive, affective, and higher-order thinking skills, particularly critical thinking in elementary IPAS learning. However, in practice, learning activities are still predominantly teacher-centered, resulting in low student engagement and suboptimal development of critical thinking skills. In addition, the use of instructional models that are not aligned with students’ developmental characteristics further contributes to this issue. This study aims to examine the effectiveness of the Problem Based Learning (PBL) model in improving students’ critical thinking skills in elementary IPAS learning. The research employs a Systematic Literature Review (SLR) method by analyzing relevant articles published between 2015 and 2026 obtained from Google Scholar, Garuda, and SINTA databases. The selection process follows PRISMA stages, including identification, screening, eligibility, and inclusion, resulting in 10 selected articles. Data were analyzed using descriptive qualitative synthesis to identify patterns, similarities, and differences in findings. The results indicate that the implementation of PBL consistently has a positive impact on improving students’ critical thinking skills, as evidenced by increased average scores, percentages, and categories of critical thinking abilities. Moreover, PBL enhances student engagement and promotes active learning through contextual problem-solving activities. Therefore, PBL can be considered an effective instructional model to improve critical thinking skills in elementary school students.